Avaliação de desempenho do modelo de turbulência k-w SST para dispersão de poluentes ao redor de obstáculo cúbico em diferentes condições de estabilidade atmosférica - Costa, Israel Bahia (2016)
The main objective of this study is to evaluate the performance of the turbulence model k-ω SST (Shear Stress Transport), by means of numerical simulations based on the solution of the conservation equations (mass, momentum, energy and chemical species). We investigated the flow and dispersion of gaseous isolated compounds around the cubic obstacle, under neutral atmospheric stability conditions, both stable and unstable. The finite volume method with unstructured mesh formed by tetrahedral and prismatic volume elements is used for the numerical solution of the conservation equations through the use of the commercial software for computational fluid dynamics, Ansys Fluent. Two experimental configurations published in the scientific literature were simulated: (i) wind tunnel (MURAKAMI et al, 1990) with Reynolds number (Re) based on the height of the obstacle (H) and speed H approximately equal to 60000 used to test the sensitivity of the empirical constants of the turbulence model (influence in the turbulent viscosity) and (influence on the limitation of the production of the turbulent kinetic energy production in stagnant zones ) and to compare with other turbulent models (ii) field experiment (MAVROIDIS et al., 1999) with Re ≈ 70000, in order to evaluate the influence of the atmospheric stability conditions of the plume contaminants and the concentration of decay after the interruption of the emission. In this case, the empirical constants that produced the best experiment Murakami et al. (1990) were used. It was observedthe influence of empirical constants for the prediction of recirculation zone length behind the building and aprediction of turbulent kinetic energy when compared withother turbulence models. The concentration fields had good agreement with the experimental data Mavroidis et al. (1999). The turbulence model k-ω SST overestimated the compound residence time in the turbulent wake when compared with the experimental results in the field, although it had slightly smaller percentage errors that other turbulence model (k-l) that were previously simulated Mavroidis et al. (2012).The atmospheric stability not significantly influence the plume of contaminants to the scenarios evaluated. The most significant impact was related to the intensity of the wind velocity. Thus, the presence of the obstacleseems toinfluence more significantly the turbulence intensity due to shear stresses than atmospheric stability by means of thermal buoyancy.